Implementation of Tikrar Methods in Memorizing Al-Qur’an in Tahfidzul Qur’an Foundation Al-Fawwaz Medan - Rahayu Budianti; Mardianto Mardianto; Zulheddi Zulheddi (BIRCU, 2020)
Muslims as a people who are given a holy book complete with all the instructions covering all aspects of life and universal, of course the basis of Islamic education is sourced from the philosophy of life based on the Qur'an. To protect the Qur'an one way is to memorize it.This research belongs to the type of qualitative research. The data used are primary data obtained through the process of extracting data by the method of documentation, observation and interviews. Data were analyzed by descriptive-qualitative method. As for checking the validity of the data using tringulation techniques.The results of this study indicate: (1) the planning process before memorizing the Qur'an is carried out various preparations including preparing media such as the Al-Qur`an Tikrar, designing an academic calendar and preparing a book of muktabaah. (2) Implementation of the tikrar method is carried out with the help of muhafidz/muhafidzah. The technical is to repeat the verse approximately 40 times according to the target after that, deposit it to muhafdiz / dzah. (3) the effectiveness of this method can be seen from the ease with which this method is applied in institutions because it is suitable for use by students at the elementary school level. legality of the institution. The inhibiting factor is indiscipline at the time of arrival. And the catching power of different santri. The solution to deal with these obstacles is by holding meetings with parents and giving punishment to students who are late.